Arteriovenous fistula: a rare complication of distal radial access for coronary angiography - Ghali, Mark; Alzuhairi, Karam S.; Hyasat, Kais; Dunn, Richard F.; Asrress, Kaleab (International Journal of Research in Medical Sciences, 2020)
Distal radial access is an emerging alternative approach for coronary angiography, preferred for its reduced complications and time to haemostasis, and improvement of patient and operator comfort. Arteriovenous fistula formation is a very rare complication following this approach, which requires recognition but which can be managed conservatively in certain instances.